Radiomics and Radiogenomics in Evaluation of Colorectal Cancer Liver Metastasis - Wang, Yun; Ma, Lu-Yao; Yin, Xiao-Ping; Gao, Bu-Lang (Frontiers in Oncology, 2022)
Colorectal cancer is one common malignant tumor in the digestive system, and the most common approach of blood metastasis of colorectal cancer is through the portal vein system to liver. Early detection and treatment of liver metastasis is the key to improving the prognosis of the patients. Radiomics and radiogenomics use non-invasive methods to evaluate the biological properties of tumors by deeply mining the texture features of images and quantifying the heterogeneity of metastatic tumors. Radiomics and radiogenomics have been widely used in the detection, treatment, and prognosis evaluation of colorectal cancer liver metastases. Based on the imaging features of liver, this paper reviews the current situation and application of radiomics and radiogenomics in colorectal cancer liver metastases.